Penerapan Media Permainan Congklak dalam Meningkatkan Belajar Matematika dengan Materi Faktor dan Kelipatan di Kelas 5 SDN Sukatenang 03 - Abdullah, Mohamad Syarief (Cipta Media Harmoni, 2025)
The background of this research focuses on the importance of innovation in mathematics learning methods, particularly in addressing students' difficulties in understanding abstract concepts such as common multiples. Recent studies indicate that many elementary school students struggle to grasp the concept of common multiples, which impacts their comprehension of more advanced mathematical material. This research aims to investigate the effectiveness of using the congklak (traditional Indonesian board game) as a learning medium to enhance students' understanding of common multiples in Grade 5 at SD Sukatenang 03. Methods: The method used is classroom action research (CAR), which involves collaboration between the researcher and the teacher to plan, implement, and evaluate the learning process. The results of the study indicate that the use of the congklak game has a significant positive impact on students' understanding, with improvements in engagement, motivation, and positive attitudes toward learning mathematics. This study confirms that the congklak game is an effective and engaging innovative learning medium, capable of enhancing the quality of mathematics education at the elementary school level.